Intraperitoneal cisplatin versus no further treatment: 8-year results of EORTC 55875, a randomized phase III study in ovarian cancer patients with a pathologically complete remission after platinum-based intravenous chemotherapy. (1st October 2003) - Piccart, M. J.; Floquet, A.; Scarfone, G.; Willemse, P. H. B.; Emerich, J.; Vergote, I.; Giurgea, L.; Coens, C.; Awada, A.; Vermorken, J. B.
Abstract : First-line intravenous chemotherapy (CT) following debulking surgery is associated with prolonged survival, in particular in patients who achieve a pathological complete remission (pCR) at second-look surgery but in whom a high rate of relapses still occurs. Between 1988 and 1997, 153 patients in pCR following platinum-based intravenous CT were randomized between four courses of intraperitoneal cisplatin (P) (90 mg/m 2 every 3 weeks) or observation. Overall survival (OS) was the primary endpoint, while progression-free survival (PFS) was a secondary endpoint. This intent-to-treat analysis includes 16 patients who were not eligible and 17 patients who had protocol violations. The two groups were well balanced in terms of age (median = 55 years), performance status (78% P.S. O), FIGO stage (96% stage III), histology (serous in 66%), grade (2 or 3 in 80%), and residuum before intravenous CT (>1 cm in 40%). Intraperitoneal CT was delivered mainly through intraperitoneal catheters (Port-a-Cath 61% and Tenckhoff 25%). Side effects of intraperitoneal cisplatin included vomiting [≥grade 2 (82%)], rise in serum creatinine [≥grade 2 (14%)], abdominal pain [grade 1–2 (38%)], and neurotoxicity [grade 2–3 (15%)]. After a median follow-up of 8 years, 80 patients (52%) have progressed with no difference in the pattern of relapse between the two groups and 75 patients (49%) have died; the respective hazard ratios for PFS and OS with 95% CI are 0.89 (0.59–1.33) and 0.82 (0.52–1.29). These results are suggestive of a treatment benefit but do not support a change in clinical practice. Other randomized clinical trials of intraperitoneal CT are reviewed and briefly discussed.